2015
DOI: 10.3934/dcdsb.2015.20.1077
|View full text |Cite
|
Sign up to set email alerts
|

A detailed balanced reaction network is sufficient but not necessary for its Markov chain to be detailed balanced

Abstract: Certain chemical reaction networks (CRNs) when modeled as a deterministic dynamical system taken with mass-action kinetics have the property of reaction network detailed balance (RNDB) which is achieved by imposing network-related constraints on the reaction rate constants. Markov chains (whether arising as models of CRNs or otherwise) have their own notion of detailed balance, imposed by the network structure of the graph of the transition matrix of the Markov chain. When considering Markov chains arising fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 20 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…As an immediate consequence of Corollary 4.10 and Theorem 5.6, the following can be stated, in the spirit of Theorem 5.2 (due to [15]):…”
Section: (Stochastic Reaction Vector Balance =⇒mentioning
confidence: 91%
See 1 more Smart Citation
“…As an immediate consequence of Corollary 4.10 and Theorem 5.6, the following can be stated, in the spirit of Theorem 5.2 (due to [15]):…”
Section: (Stochastic Reaction Vector Balance =⇒mentioning
confidence: 91%
“…In [1] it is further proven that such models are non-explosive. In [15] it is proven that if an ODE model with mass action kinetics has a positive detailed balanced equilibrium, then the stationary distributions of the corresponding Markov chain model are detailed balanced, in the classical probabilistic sense [21]. Finally, in [7] it is shown that if an ODE model with mass action kinetics is complex balanced, then the stochastic counterpart has a so called complex balanced stationary distribution, and the converse holds as well.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems must be coupled to implicit reservoirs of fuel molecules that can drive the species of interest into a non-equilibrium steady state [41,42,43]. Usually -but not always [44,45] -the resultant Markov chain violates detailed balance. In Section 3.1, we shall consider a system that exhibits detailed balance at the level of the Markov chain, but is necessarily non-equilibrium and violates detailed balance at the detailed chemical level.…”
Section: Detailed Balanced Chemical Reaction Networkmentioning
confidence: 99%
“…For example, in chemical mass action law kinetics we can consider the reaction mechanism A ⇋ B (rate constants k ±1 ), A + B ⇋ 2B (rate constants k ±1 ) [22]. We can also create a stochastic model for this system with the states (xA, yB) (x, y are nonnegative integers) and the elementary transitions (xA, yB) ⇋ ((x − 1)A, (y + 1)B) (rate constants κ + = k +1 x + k +2 x 2 , κ − = k −1 (y + 1) + k −2 (x − 1)(y + 1)).…”
Section: Sampling Of Different Macro-events From the Same Micro-eventsmentioning
confidence: 99%
“…Thus, macroscopic detailed balance may be violated in this example when microscopic detailed balance holds. (For more examples and theoretic consideration of the relations between detailed balance in mass action law chemical kinetics and stochastic models of these systems see [22].) Indeed, both of the macroscopic elementary processes A ⇋ B and A + B ⇋ 2B correspond to the same set of microscopic elementary processes (xA, yB) ⇋ ((x − 1)A, (y + 1)B).…”
Section: Sampling Of Different Macro-events From the Same Micro-eventsmentioning
confidence: 99%